Novel mutation in the KCNJ10 gene in three siblings with seizures, ataxia and no electrolyte abnormalities. (2nd January 2018) - Al Dhaibani, Muna A.; El-Hattab, Ayman W.; Holroyd, Kathryn B.; Orthmann-Murphy, Jennifer; Larson, Valerie A.; Siddiqui, Khurram A.; Szolics, Miklos; Schiess, Nicoline
Abstract: We report a consanguineous family with three affected siblings with novel mutation in the KCNJ10 gene. All three presented with central nervous system symptoms in the form of infantile focal seizures, ataxia, slurred speech with early developmental delay and intellectual disability in two siblings. None had any associated electrolyte abnormalities and no symptomatic hearing deficits were observed.